The interrelation of CYP2C9, CYP4F2, VKORC1 genes polymorphisms with warfarin dose and hemorrhagic complications risk rise in patients with atrial fibrillation: a retrospective study - Kolesnyk, M.; Mykhailovskyi, Ya. M.; Колесник, Михайло Юрійович (My University, 2021)
The aim of the studywas to identify the frequency of CYP2C9, CYP4F2, VKORC1 genes polymorphisms in patients with atrial fibrillation(AF) and to establish their interrelationship with warfarin (WF)dose and the hemorrhagic complications risk rise.Materials and methods. A retrospective study was conducted in 60AF patients receiving WF during one year. CYP2C9, CYP4F2, VKORC1 genes polymorphisms were studied by multiplex real time polymerase chain reaction.Obtained results. The mean CHA2DS2-VASC score was 3.43± 0.18, HAS-BLED score –2.2± 0.13; the WF dose median was 5mg (3.75; 6.25). It was found out that the VKORC1 mutant allele A presence increased the probability of WF dose less than median in 7.00 times (95% CI 1.982-24.716; p <0.05), and the CYP4F2 mutant allele T increased the probability of WF dose more than median in 6.263 times (95% CI 1.583-24.780). Statistically significant effect of CYP2C9 gene polymorphism on WF dosing was not observed. Bleeding was significantly more frequent in the group of patients with the VKORC1 gene mutation: 69.5% versus 37.5%, respectively (χ2= 5.331; p <0.05). The relative risk of bleeding in patients with the VKORC1 gene mutation was 1.97 (CI 1.039; 3.751; p <0.05).Conclusions.VKORC1 and CYP4F2 genes polymorphisms are associated with warfarin dose variation. VKORC1 gene mutation increases the risk of bleeding.ЦельюисследованиябыловыявитьчастотуполиморфизмовгеновCYP2C9, CYP4F2, VKORC1 упациентовсфибрилляциейпредсердий(ФП) иустановитьихвзаимосвязьсдозойварфарина (ВФ)иповышениемрискагеморрагическихосложнений.Материалы и методы. Ретроспективное исследование проведено у 60 пациентов с ФП, получавших ВФ в течение одного года. Полиморфизмы генов CYP2C9, CYP4F2, VKORC1 изучали методом мультиплексной полимеразной цепной реакции в режиме реальноговремени. 38East European ScientificJournal #1(65), 2021Полученыерезультаты. Средний балл CHA2DS2-VASC составил 3,43 ± 0,18, балл HAS-BLED -2,2 ± 0,13; медиана дозы ВФсоставила5 мг (3,75; 6,25). Обнаружено, что наличие мутантного аллеля A VKORC1 увеличивало вероятность дозы ВФменьше медианы в 7,00 раз (95% ДИ 1,982-24,716; p<0,05), амутантный аллель T CYP4F2 увеличивал вероятность дозы ВФбольше медианы в 6,26 раза (95% ДИ 1,583-24,780). Статистически значимого влияния полиморфизмов гена CYP2C9 на дозу ВФне наблюдалось. Кровотечения достоверно чаще возникали в группе пациентов с мутацией гена VKORC1: 69,5% против 37,5% соответственно (χ2= 5,331; p<0,05). Относительный риск кровотечения у пациентов с мутацией гена VKORC1 составил 1,97 (CI 1,039; 3,751; p <0,05).Выводы. Полиморфизмы генов VKORC1 и CYP4F2 связаны с вариацией дозы варфарина. Мутация гена VKORC1 увеличивает риск возникновения кровотечений.
Keywords: atrial fibrillation; warfarin; dosing; genes; bleeding; фибрилляция предсердий; варфарин; дозировка; гены; кровотечение